Plasticity in the Brainstem: Prenatal and Postnatal Experience Can Alter Laterodorsal Tegmental (LDT) Structure and Function - Kohlmeier, Kristi A.; Polli, Filip S. (Frontiers in Synaptic Neuroscience, 2020)
The brainstem has traditionally been considered an area of the brain with autonomous control of mostly homeostatic functions such as heart rate, respiration, and the sleep and wakefulness state, which would preclude the necessity to exhibit the high degree of synaptic or cellular mechanisms of plasticity typical of regions of the brain responsible for flexible, executive control, such as the medial prefrontal cortex or the hippocampus. The perception that the brainstem does not share the same degree of flexibility to alter synaptic strength and/or wiring within local circuits makes intuitive sense, as it is not easy to understand how “soft wiring” would be an advantage when considering the importance of faithful and consistent performance of the homeostatic, autonomic functions that are controlled by the brainstem. However, many of the molecular and cellular requirements which underlie strengthening of synapses seen in brain regions involved in higher-level processing are present in brainstem nuclei, and recent research suggest that the view of the brainstem as “hard wired,” with rigid and static connectivity and with unchanging synaptic strength, is outdated. In fact, information from studies within the last decades, including work conducted in our group, leads us to propose that the brainstem can dynamically alter synaptic proteins, and change synaptic connections in response to prenatal or postnatal stimuli, and this would likely alter functionality and output. This article reviews recent research that has provided information resulting in our revision of the view of the brainstem as static and non-changing by using as example recent information gleaned from a brainstem pontine nucleus, the laterodorsal tegmentum (LDT). The LDT has demonstrated mechanisms underlying synaptic plasticity, and plasticity has been exhibited in the postnatal LDT following exposure to drugs of abuse. Further, exposure of the brain during gestation to drugs of abuse results in alterations in development of signaling pathways in the LDT. As the LDT provides a high degree of innervation of mesoaccumbal and mesocortical circuits involved in salience, as well as thalamocortical circuits involved in control of arousal and orientation, changes in synaptic strength would be expected to alter output, which would significantly impact behavioral state, motivated behavior and directed attention. Further, alterations in developmental trajectory within the LDT following prenatal exposure to drugs of abuse would be expected to impact on later life expression of motivation and arousal.